The Integration of Language and Content: Form-Focused Instruction in a Content-Based Language Program - Valeo, Antonella (Canadian Journal of Applied Linguistics, 2013)
Abstract This comparative, classroom-based study investigated the effect and effectiveness of introducing a focus on form approach to a content-based, occupation-specific language program for adults. Thirty-six adults in two classes participated in a 10-week study. One group of 16 adults received content-based instruction that included a focus on form component while the other group of 20 adults received the same content-based instruction with a focus on meaning only. Pre-tests/post-tests/delayed post-tests measured learning of two grammatical forms, the present conditional and the simple past tense, as well as occupational content knowledge. Results indicated significant gains on most of the language measures for both learner groups but significant advantages for the form-focused group on the content knowledge tests. The results are discussed in relation to the impact of specific strategies designed to focus on form and the relationship between attention to form and comprehension of content in the context of content-based language programs. Résumé Cette étude comparative menée en salle de classe a examiné l’effet et l’efficacité d’un enseignement mettant l’accent sur ​​la forme dans un programme de langues professionnelles pour adultes. Trente-six apprenants de deux classes intactes ont participé à cette recherche pendant 10 semaines. Un groupe de 16 personnes a reçu les instructions qui se concentraient sur la forme, tandis que l’autre groupe de 20 personnes a reçu les mêmes instructions qui portaient sur ​​le sens seulement. Des pré-tests, des post-tests ainsi que des post-tests retardés ont mesuré l’apprentissage de la langue et du contenu de deux traits grammaticaux; premièrement, la connaissance du conditionnel et du passé et, deuxièmement, la connaissance du contenu professionnel. Les résultats ont indiqué une amélioration sensible de la plupart des compétences linguistiques pour les deux groupes d’étudiants. Or, le groupe ayant mis l’accent sur la forme a connu des progrès significatifs aux tests de connaissance du contenu. Les résultats examinés se basent sur l’impact des stratégies spécifiques visant à faire ressortir la forme ainsi que la relation entre l’attention portée à la forme et la compréhension du contenu dans ce contexte particulier.